Arterial Calcification on Wrist Radiographs May Suggest Need for Evaluation of Atherosclerosis in Asymptomatic Individuals. (3rd July 2019) - Watchmaker, Lauren E.; Watchmaker, Jennifer M.; Watchmaker, Greg P.
Abstract : Asymptomatic individuals with significant coronary artery disease (CAD) are at risk for unanticipated cardiac events including myocardial infarction (MI). Laboratory studies, stress tests, and coronary artery imaging including coronary artery calcium (CAC) scoring evaluate at-risk individuals. Hand and wrist x-rays demonstrating significant arterial wall calcification may provide an additional means to identify asymptomatic individuals at risk for cardiac events. Here we report a case series of patients without known cardiac disease who demonstrated significant calcium deposits in the radial and/or ulnar arteries in radiographs performed for evaluation of their hand conditions. Each series patient was subsequently found to have calcification on coronary artery imaging and an elevated risk of future cardiac events. Our series suggests that peripheral arterial calcifications observed by radiologists and hand specialists may warrant systemic evaluation for atherosclerosis in other areas of the body.